An Investigation of Excited-State Intramolecular Proton Transfer Mechanism of New Chromophore (Journal of Atomic and Molecular Sciences, 2018)
Based on the time-dependent density functional theory (TDDFT), the excitedstate intramolecular proton transfer (ESIPT) mechanism of a new compound 1chromophore synthesized and designed by Liu et al. [Journal of Photochemistry andPhotobiology B: Biology., 138 (2014), 75-79] has been investigated theoretically. Thecalculations of primary bond lengths, angles and the IR vibrational spectra verifiedthe intramolecular hydrogen bond was strengthened. The fact that reproduced theexperimental absorbance and fluorescence emission spectra well theoretically demonstratesthat the TDDFT theory we adopted is reasonable and effective. In addition,intramolecular charge transfer based on the frontier molecular orbitals demonstratedthe indication of the ESIPT reaction. The constructed potential energy curves of groundstate and the first excited state based on keeping the O-H distance fixed at a serious ofvalues have been used to illustrate the ESIPT process. A little barrier of 2.45 kcal/molin the first excited state potential energy curve provided the transfer mechanism. Further,the phenomenon of fluorescence quenching has been explained reasonably basedon the ESIPT mechanism.